Spatial suitability of tourist sites in the Lattakia region: Comparison between Kassab and Mashkita sites - جوني, رهف; خضرة, جلال بدر (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Latakia region has many natural, geographical and historical tourist characteristics. It also has many competitive advantages tourist such as mountainous areas, coastal areas, and various other possibilities such as tourist sites and services. This study aims to determine the tourism characteristics of each of the sites of Kassab and Mashkita - which are two important tourist sites in the Lattakia region and are distinct in terms of location and tourist characteristics - using geographic information system (GIS), and then evaluate the tourism potential of each site in order to make a comparison between them according to a set of the criteria and factors are: landscape (visibility, land uses), topography (elevation, slope), accessibility (proximity to tourist sites and services, distance from roads). the land suitability map for tourism was created, based on the combination of the criteria and factors with their respective weights. The degree of suitability of each factor was classified as highly suitable (S1), moderately suitable (S2), lowly suitable (S3) and not suitable (N) for tourism.